Liposomal Bupivacaine Suspension Can Reduce Lengths of Stay and Improve Discharge Status of Patients Undergoing Total Knee Arthroplasty - Chughtai, Morad; Cherian, Jeffrey Jai; Mistry, Jaydev B.; Elmallah, Randa D. K.; Bennett, Alicia; Mont, Michael A. (The Journal of Knee Surgery, 2016)
The purpose of this study was to use a large hospital database to assess: (1) length of hospital stay (LOS) and (2) discharge status among patients undergoing total knee arthroplasty (TKA) with or without the use of a liposomal bupivacaine suspension injection. We utilized an all-payer hospital administrative database from July 1, 2013 to June 30, 2014. We then selected patients age 18 years or older who had an inpatient stay for TKA in the data window based on International Classification of Diseases, Ninth Revision (ICD-9) procedure codes (ICD-9-CM = 81.54), which resulted in 103,152 TKA patients. Patients who had nerve blocks were excluded, which resulted in 94,828 TKA patients. The TKA cohort who received a liposomal bupivacaine suspension consisted of 14,668 patients (9,211 females; 5,457 males) who had a mean age of 66 years, while the TKAs without injections or block consisted of 80,160 patients (49,699 females; 30,461 males) who had a mean age of 66 years. Analyses of LOS were performed using a linear model, controlling for age, sex, race, region, Charlson index, and operating time. Discharge status to home versus rehabilitation or short-term nursing facility was evaluated using logistic regression analysis controlling for the above covariates. The adjusted mean LOS for the injection cohort was significantly shorter at 2.58 days compared with 2.98 days in the no injection cohort. The unadjusted distribution of patients being discharged to home compared with short-term nursing facility or rehabilitation was higher in the injection cohort compared with the cohort who did not receive injections (73.2 vs. 66.6%). Logistic regression analysis demonstrated that there was a higher likelihood of being discharged to home with liposomal bupivacaine. Patients who underwent TKA with liposomal bupivacaine had a significantly shorter LOS and a higher likelihood of being discharged to home. These results suggest that liposomal bupivacaine may represent a promising addition to current pain management regimens. Furthermore, it may limit pain following surgery, which may allow patients to ambulate earlier and have improved outcomes.
Keywords: total knee arthroplasty; liposomal bupivacaine; TKA; pain